Ploidy in bone marrow cells from healthy donors: a MAC (morphology antibody chromosomes) study - Larramendy, Marcelo Luis (1994)
The ploidy of human bone marrow cells belonging to the megakaryocytic, granulocytic-monocytic and erythrocytic lineages was studied by in situ hybridization using the biotin-labelled Y chromosome-specific DNA probe pY431 and the chromosome 1-specific probe pUC1.77 on cells identified morphologically and immunologically by the MAC procedure. Cells of the granulocytic-monocytic and erythrocytic lineages were seen to be 2N in ploidy, whereas the ploidy of the megakaryocytic lineage ranged from 2N to 32N, with the ploidy classes 4N and 8N being predominant. The frequency of megakaryocytes with 2N chromosomes was also high.